PILATES EXERCISE DAPAT MENURUNKAN INDEKS MASSA TUBUH (IMT) PEREMPUAN OBESITAS TINGKAT 1 DI PERUMAHAN BUMI DIRGANTARA PERMAI BEKASI - Dwi Agustina; Nikky Novannisa (Poltekkes Kemenkes Jakarta III, 2017)
The prevalence of obesity is tend to increase both in the world and in Indonesia, and a higher prevalence in women. Obesity is a risk factor of various degenerative diseases such as coronary heart disease and stroke, musculoskeletal disorders, especially osteoarthritis, diabetes mellitus and cancer. One exercise that is appropriate for treating obesity is Pilates exercise which is a muscle contraction exercises that are low impact. The aim of this study was to determine the effect of Pilates Exercise on obese level 1 women's body mass index. The type of research was experimental with pre-experimental research design. The experiment was conducted in late April-May 2016 in Bumi Dirgantara Permai. The number of sample was 15 obese level 1women. Pilates exercises was given for one hour three times a week for 5 weeks. Analysis of the data include univariate and bivariate with the Kolmogorov-Smirnov test for checking normality data and Paired t-test for testing IMT different before and after intervention. Results: The mean BMI before intervention was 25.74 kg / m2 and after the intervention of 26.44 kg / m2. The reduction in BMI of 0.7 kg / m2, with test results p value of 0.0001 indicated the difference in IMT before and after the intervention were significant. Conclusion:To maintain the IMT and improve posture, Pilates Exercise should be done regularly.